FASHION, JILBAB: BETWEEN RELIGIOSITY AND CAPITALISM, A CASE STUDY OF HIJABERS SURABAYA: FASHION, JILBAB: ANTARA AGAMA DAN KAPITALISME, STUDI KASUS HIJABERS SURABAYA - Choirul Chamdiyatus Sholichah (SOSIOEDUKASI, 2020)
Hijabers Surabaya is a community of veiled women who become the mecca for young Muslim fashion . They are continuously creating the hijab with the latest fashions. Hijabs by Hijabers Surabaya are generally priced quite expensive. This situation raises the curiosity of researchers. How do Hijabers Surabaya present their lifestyle. And how is the relevance between fashion, hijab and capitalism in Hijabers Surabaya. To answer these problems, this study uses qualitative methods with the type of case study research. This qualitative research method was chosen in order to obtain in-depth and comprehensive research data regarding the lifestyle of Surabaya Hijabers and the relevance of fashion, headscarves and capitalism in Hijabers Surabaya. The data obtained were then presented descriptively and then analyzed with the social construction theory coined by Peter L. Berger.